Q: 5x-8 equals -2x plus 6

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

x = 8y = 6(5x8) + (3x6) = 58(5x8) - (3x6) = 22

2x + 1 = 13; 2x = 12; x = 6

-3x + 2x = 6Let's abbreviate left part by cancellation:-x = 6The answer will be:x = -6

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

5X + 6 = 2X + 15 -2X -2X 3X + 6 = 15 -6 -6 3X = 15 ---- ----- 3 3 x = 5 im so smart.

Related questions

x=1

x = 8y = 6(5x8) + (3x6) = 58(5x8) - (3x6) = 22

8x-7 plus 2x equals 6 plus 5x plus 2?

-2x-6= -2x-6Another answer:-2x-6 = 2x+6-2x-2x = 6+6-4x = 12x = -3

2x-11

5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2

4x+35-2x+25 = 6 2x+60 = 6 2x = 6-60 2x = -54 x = -27

6y

2x+2=x+6 first subtract 2x. -2x -2x2=-1x+6 then subtract 6-6 -6-4=-1x finally divide by -1x=4 X equals four.

DIE

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

22+2x = 37+6+x 2x-x = 37+6-22 x = 21